Young Malaysian Consumers’ Attitude and Intention to Imitate Korean Celebrity Endorsements - Wan Roazha, Wan Mat; Hyung, Jun Kim; Ahmad Azaini, Abdul Manaf; Azaze-Azizi, Abdul Adis (MAG Scholar, 2019)
This study addressed the issue of young Malaysian consumers’ intention to imitate Korean celebrities’ endorsement in advertisements. The researchers specifically focused on the impact of Korean celebrity characteristics and the consumer’s individual characteristics on the latter’s attitude towards imitating celebrity endorsements and the consumer’s intention to imitate. 602 young Malaysian consumers in the Klang Valley participated in this study. The results pointed to celebrity characteristics namely attractiveness and trustworthiness as directly and indirectly significant, whilst credibility and expertise were directly and indirectly not significant predictors on consumer attitude toward imitating celebrity endorsements. In addition, individual characteristics namely self-satisfaction and expression of power were directly and indirectly significant predictors on consumer attitude towards imitating celebrity endorsements. There was also a significant effect on attitude towards imitating celebrity endorsements on intention to imitate. Suggestions for future research are discussed at the end of this paper.